Targeting hidden pathogens: Cell-penetrating enzybiotics eradicate intracellular drug-resistant staphylococcus aureus - Christian Röhrig (2020)
© 2020 Röhrig et al. Staphylococcus aureus is a major concern in human health care, mostly due to the increasing prevalence of antibiotic resistance. Intracellular localization of S. aureus plays a key role in recurrent infections by protecting the pathogens from antibiotics and immune responses. Peptidoglycan hydrolases (PGHs) are highly specific bactericidal enzymes active against both drug-sensitive and-resistant bacteria. However, PGHs able to effectively target intracellular S. aureus are not yet available. To overcome this limitation, we first screened 322 recombineered PGHs for staphylolytic activity under conditions found inside eukaryotic intracellular compartments. The most active constructs were modified by fusion to different cell-penetrating peptides (CPPs), resulting in increased uptake and enhanced intracellular killing (reduction by up to 4.5 log units) of various S. aureus strains (including methicillin-resistant S. aureus [MRSA]) in different tissue culture infection models. The combined application of synergistic PGH-CPP constructs further enhanced their intracellular efficacy. Finally, synergistically active PGH-CPP cocktails reduced the total S. aureus by more than 2.2 log units in a murine abscess model after peripheral injection. Significantly more intracellular bacteria were killed by the PGH-CPPs than by the PGHs alone. Collectively, our findings show that CPP-fused PGHs are effective novel protein therapeutics against both intracellular and drug-resistant S. aureus. IMPORTANCE The increasing prevalence of antibiotic-resistant bacteria is one of the most urgent problems of our time. Staphylococcus aureus is an important human pathogen that has acquired several mechanisms to evade antibiotic treatment. In addition, S. aureus is able to invade and persist within human cells, hiding from the immune response and antibiotic therapies. For these reasons, novel antibacterial strategies against these pathogens are needed. Here, we developed lytic enzymes which are able to effectively target drug-resistant and intracellular S. aureus. Fusion of these so-called enzybiotics to cell-penetrating peptides enhanced their uptake and intracellular bactericidal activity in cell culture and in an abscess mouse model. Our results suggest that cell-penetrating enzybiotics are a promising new class of therapeutics against staphylococcal infections.